How integrated are the European retail financial markets? A cointegration analysis - Friedrich Heinemann; Martin Schüler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
With the introduction of the Euro, a single European money market has emerged. Further wholesale financial markets are considered to be highly integrated within the European Union. However, integration in retail financial markets is less advanced. For measuring financial market integration this distinction between wholesale and retail markets becomes crucial. There is a wide literature relating to integration of wholesale financial markets but just a few studies that try to measure integration in European retail markets. This paper, in a first step, gives a systematisation of the literature on measuring financial market integration with a focus on the distinction between wholesale and retail financial markets. In a second step, bivariate and multivariate cointegration techniques are used to assess the degree of integration in four loans and two deposit markets in the European Union. Finally, based on this analysis obstacles to financial market integration are discussed.
Keywords: G15; F36; 330; Financial Market Integration; Cointegration; European Union; Retail Banking; Internationaler Finanzmarkt; Marktintegration; Kointegration; Schätzung; EU-Staaten